A century of Public Administration: Traveling through time and topics. (27th February 2022) - Vogel, Rick; Hattke, Fabian
Abstract: Public Administration (PA) has been a unique witness and protagonist of scholarship in the field of public administration over the course of an entire century. On the occasion of the journal's 100th anniversary, we conduct a systematic analysis of the publication history using bibliometric methods enhanced by natural language processing. The findings show how disciplinary influences, geographical settings, and methodological orientations have changed over time. In our main analysis, we extract 63 thematic clusters on the basis of linguistic similarities and track their evolution through five eras of PA scholarship. Overall, the results show both the journal's strong British roots and its evolvement toward an increasingly international, interdisciplinary, and dynamic community. The findings also indicate the state of the field as a "fragmented adhocracy, " with changing modes of differentiation over time.